The Art of Balance: A Corpus-assisted Stylistic Analysis of Woolfian Parallelism in «To the Lighthouse» - Zhao, Mingzhu (International Journal of English Studies, 2012)
This study has a two-fold objective: 1) to examine the density and variety of parallelism in Virginia Woolf’s landmark novel To the Lighthouse through a sample-based comparison between this novel and other representative modernist novels; 2) to discuss the specific lexical and syntactic structures that characterize Woolf’s parallelism. The results are extracted from a corpus-assisted reading and sampled textual analysis of her work. It shows that Woolfian parallelism is defined by an abundance of antithetical and synonymous lexical bundles, juxtaposed propositional phrases, -ing participles and appositional structures. Those structures constitute her special sentential development which is marked by the rhetoric of opposition, the rhetoric of simultaneity and progression, and the rhetoric of specificity. It is concluded that in To the Lighthouse, Woolf manipulates the above-mentioned linguistic resources to strike an artistic balance between poetry and prose, order and chaos, the physical reality and the mental world, and finally achieves what she calls “a feminine sentence”.